Enheduanna – A Manifesto of Falling: first demonstration of a live brain-computer cinema performance with multi-brain BCI interaction for one performer and two audience members. Issue 2 (3rd April 2017) - Zioga, Polina; Chapman, Paul; Ma, Minhua; Pollick, Frank
ABSTRACT: The new commercial-grade Electroencephalography (EEG)-based Brain-Computer Interfaces (BCIs) have led to a phenomenal development of applications across health, entertainment and the arts, while an increasing interest in multi-brain interaction has emerged. In the arts, there is already a number of works that involve the interaction of more than one participants with the use of EEG-based BCIs. However, the field of live brain-computer cinema and mixed-media performances is rather new, compared to installations and music performances that involve multi-brain BCIs. In this context, we present the particular challenges involved. We discuss Enheduanna – A Manifesto of Falling, the first demonstration of a live brain-computer cinema performance that enables the real-time brain-activity interaction of one performer and two audience members; and we take a cognitive perspective on the implementation of a new passive multi-brain EEG-based BCI system to realise our creative concept. This article also presents the preliminary results and future work.